Pengkajian Kemampuan Gabungan Wild Teodolit TI Dan Leica Distotm Classic Untuk Survei 3 Dimensi - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Energi UGM, 2005)
ABSTRAK Teodolite can be used to map indoor targets such as cave, tunnel, inside buildings as long as long as the targets con be accessed by the observer. There are off course other techniques to measure inaccessible targets but this will be time consuming of frequently setting up instrument. On the other hand, Leica Disto ClassicTM is a small handy measurement device using laser technology. This device can be used to measure inaccessible targets. Unfortunately, this device cannot provide the inclination data (vertical angle) in case of measuring the inclined targets. Combination of both teodolite and Disto may improve in case of measuring inaccessible targets. This research is meant to make such platform that the Disto can be joined with teodolite. This research also investigates the capability of combination of both which is, in this case, called TeoDisto. â¢ This research is conducted as follows: designing the platform and examining the system of TeoDisto. The platform is designed using the following constraints, 1) the Disto vizier is in line and coplanar with teodolite vizier, 2) assembled by horizontal and vertical screw, 3) the easiness of reading the Disto display, 4) economically and simply designed, 5) teodolite movement dependant, 6) Disto can be safely removed from platform host without readjusting the Disto vizier. The TeoDisto is then calibrated and accessed its capability by means measuring buildings/target in regularly forms such as class room indoor. The estimated distances obtained using TeoDisto are then compared by tape measurements. As the results, the platform can be used to joint between Disto and teodolite. Comparisons between TeoDisto and tape measurements of distances give satisfying results that are span from 0 to 4 cm. Survei 3 dimensi, Wild teodolit